2019
DOI: 10.1107/s1600577519009792
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-irradiation-induced micro-structural variations in flame-retardant polyurethane foam using synchrotron X-ray micro-tomography

Abstract: Flame‐retardant polyurethane foams are potential packing materials for the transport casks of highly active nuclear materials for shock absorption and insulation purposes. Exposure of high doses of gamma radiation causes cross‐linking and chain sectioning of macromolecules in this polymer foam, which leads to reorganization of their cellular microstructure and thereby variations in physico‐mechanical properties. In this study, in‐house‐developed flame‐retardant rigid polyurethane foam samples were exposed to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
1
4
1
Order By: Relevance
“…At first glance, the results [67][68][69] contradict the effect of pore dissolution discovered in our study in the case of PTFE irradiation in the melt. However, it was shown [70] that an increase in the irradiation temperature has a strong effect on the volume concentration, shape, and size of helium bubbles in boron carbide.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…At first glance, the results [67][68][69] contradict the effect of pore dissolution discovered in our study in the case of PTFE irradiation in the melt. However, it was shown [70] that an increase in the irradiation temperature has a strong effect on the volume concentration, shape, and size of helium bubbles in boron carbide.…”
Section: Discussioncontrasting
confidence: 79%
“…At the same time, the radiation heating of solids, which occurs as a result of the dissipation of the absorbed energy of ionizing radiation [63,68], turns out to be insufficient for the development of pore formation processes. This is confirmed by the results of a study by the method of X-ray computer microtomography of radiation-induced changes in the characteristics of the porous structure in foamed polyurethane samples, gamma-irradiated to various doses at room temperature [69]. It is shown that the observed changes in the porous structure of the polymer are caused by the processes of increasing the size of micropores and coalescence, which are caused by radiation crosslinking of macromolecules.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…(Agrawal et al, 2017;Singh et al, 2017). The facility has been successfully used for numerous applications in a variety of domains in research and industry (Chhajed et al, 2019;Thomas et al, 2019;Choudhary et al, 2018;Agrawal et al, 2019;Mishra et al, 2020;Manzoor et al, 2019;Fatima et al, 2017;Yadav et al, 2018). Monochromatic beam has been used quite successfully with advantages such as availability of diffraction enhanced imaging for high-sensitivity phase contrast, improved edge enhancement in propagation-based phase-contrast imaging, and removal of beam-hardening artefacts in tomography.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric foam materials, defined as a dispersion of gas into polymeric matrix, has the properties of low density, exceptional strength to weight ratio, lightweight, excellent thermal and acoustic insulation properties, energy absorption ability, etc. [10][11][12] These materials were reported with varied densities ranging from 1.6 to 960 K gm −3 and approximately, 70%-80% of all the commercially prepared foam is based on polyurethane, polystyrene and polyvinyl chloride. 13,14 These polymeric solid foams find wide applicability in a variety of applications including packaging, cushioning, insulation etc.…”
Section: Introductionmentioning
confidence: 99%